THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE PERFORMANCE AT TANDEM PLANTATIONS LIMITED LIABILITY COMPANY PERKEBUNAN NUSANTARA I REGIONAL 1 SUPPORTING COMPANY - Arif Setiawan; Akbar Siregar; Ihsan Effendi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Leadership is one of the important factors that determine employee performance and the ability of the organization to adapt to environmental changes, therefore effective leadership must provide direction to the efforts of all workers in achieving organizational goals. In this case, one of the various forms of leadership styles that can be a factor in increasing employee performance is transformational leadership.